Strategi Agen BSI Smart Dalam Memberikan Layanan Kepada Masyarakat Pedesaan (Studi Kasus di Kecamatan Babussalam Kabupaten Aceh Tenggara ) - Salsabila, Raisya; M Nawawi, Zuhrinal; Anggraini, Tuti (Universitas Hamzanwadi, 2024)
This research explores the role of BSI Smart agents as an extension of BSI in increasing the accessibility of banking services for communities in remote areas. By using field research methods and a qualitative approach, this research also uses SWOT analysis by looking for weaknesses, strengths, opportunities and threats in the presence of BSI SMART Laku Pandai. This research finds that BSI Smart makes financial transactions easier, provides easy services, and reaches a wider community. Apart from that, BSI Smart also provides business opportunities for agents to earn additional income. The presence of BSI Smart agents also provides financial literacy education to the public, improving their ability to manage personal finances, reducing economic risks and improving overall quality of life.